(untitled) (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY Currently, the characterisation of advanced Parkinson’s disease (APD) does not follow standardised diagnostic criteria, which complicates the evaluation of ongoing care and treatment strategies, such as eligibility for device-aided treatment (DAT). Therefore, this study aimed to determine the proportion of APD and non-advanced Parkinson’s disease (non-APD) patients treated at specialised movement disorder centres in Switzerland, to compare clinical characteristics of APD versus non-APD patients and to assess eligibility for and use of DAT. Furthermore, potential differences between the Swiss and international situation should be uncovered. METHODS OBSERVE-PD was a cross-sectional, international, observational study including 2615 patients from 128 movement disorder centres in 18 countries. For the Swiss subgroup of the study analysed here, which included 134 patients from 5 movement disorder centres, motor and non-motor symptoms, activities of daily living and quality of life were assessed as endpoints. The correlation between physician’s judgement of APD and the Delphi criteria for APD, which were developed by an international expert group, as well as the clinical burden in APD and non-APD patients and eligibility for and use of DAT were evaluated. The results for the Swiss subgroup were subsequently compared with the international full analysis set of the OBSERVE-PD study. RESULTS Based on physician’s judgement, 69.4% of patients included in the Swiss study suffered from APD. A moderate correlation between physician’s judgement and the Delphi criteria for APD was observed (Κ = 0.480, 95% confidence interval 0.317–0.642). Clinical burden was higher for APD patients, as shown by worse scores for activities of daily living, motor symptom severity, dyskinesia duration/disability, duration of “off” time, non-motor symptoms and quality of life as compared with non-APD patients (p <0.0001 for all). The Swiss data for disease burden were comparable to the international findings, except that the Swiss patients showed less “off” time. Amongst APD patients eligible for DAT, the main reason for no DAT in Switzerland was patient refusal, whereas patients needing more time to decide about it was the most frequent reason in the international analysis. CONCLUSIONS The study shows that the burden of APD in tertiary care centres in Switzerland is comparable to the international situation. Patient refusal is the main reason for no DAT amongst eligible APD patients in such centres. The identification of standard APD classification parameters and evaluation of the reasons for no DAT are relevant for optimising treatment strategies and the transition to DAT.